Synthesis and Characterization of Metal-Organic Framework as Battery Electrodes - Sutikno Madnasri; Teguh Darsono; Isa Akhlis; Heru Saputera; Meilody Indreswari; Lutfiana Maghfirotul Izza; Maria A Simangunsong; Lambang Setyo Utama; Uda Hashim (Universitas Negeri Semarang, 2023)
Metal organic framework-derived carbons (MOFDCs) are materials with great potential and can be used as electrochemical energy storage because these have a large surface area and pore structure that can be adapted to needs. MOFs have porous crystals in which metal ions or clusters are linked by organic ligands. The purpose of this study was to determine the physical and electrochemical properties of MOF5 synthesized at different temperatures. The MOFs synthesis method which is classified as complicated can be simplified and the use of hazardous solvents can be reduced by means of partial substitution using water solvents. To prepare MOFs can be done in several ways, such as liquid phase epitaxy, supersonic cold spraying, direct gas phase preparation, and interface-assisted synthesis. MOFs have applications in optics, sensing, catalysis, adsorption, and modeling, as well as electrochemical energy storage. Potential application as an interesting electrode material to be studied through the synthesis method. In this study, MOF5 was synthesized at temperatures between 200Â°C-600Â°C. To prepare MOF5, zinc nitrate tetrahydrate and acetic acid were dissolved in DMF (N, N-dimethyl formamide). The remaining precipitate (MOF) was immersed three times in DMF and three times in chloroform for 24 hours for each immersion. In general, different MOF5 synthesis affects the microstructure, elemental content, optical properties (transmittance and absorbance), electrical properties, and electrochemical properties